Accuracy improvement of electrochemical whole blood ketone sensor based on HCT compensation algorithm. Issue 16 (28th May 2020) - Zhao, Ying; Gu, Hui; Li, Hongchun; Huang, Lei; Cen, Xiaobo
Abstract: In this manuscript, we demonstrated an electrochemical test strip with HCT (hematocrit) compensation algorithm to improve the accuracy of blood ketone sensor. In the conventional electrochemical sensor, the electrochemical current was directly resolved into the concentration value of the determinant without HCT compensation. For lower or higher HCT blood sample, the measured result was inaccurate. In the proposed design, the blood impedance can be measured to estimate the HCT, which was utilized to compensate the electrochemical current to resolve the more accurate concentration of determinant. The practical blood sample tests demonstrated the proposed design can provide more believable and reliable measured result in clinical point‐of‐care setting.